Water, sanitation, and hygiene services in health care facilities in the Autonomous Province of Vojvodina, Serbia. (17th November 2021) - Bijelović, Sanja; Grossi, Valentina; Shinee, Enkhtsetseg; Schmoll, Oliver; Jovanović, Dragana; Paunović, Katarina; Dragić, Nataša; Velicki, Radmila
Abstract: Provision of safe water, sanitation, and hygiene (WASH) services in health care facilities is a priority at the global, national, and local levels. To inform improvements planning, conditions of WASH, waste management, and environmental cleaning were assessed in 81 facilities in the Autonomous Province of Vojvodina, Serbia, as part of a nationally representative survey in 2019. The survey included on-site checks, structured interviews, and drinking-water quality analysis. WHO/UNICEF indicators for WASH service levels and an advanced service level defined at the national level were applied. The results showed that all investigated facilities provided basic water services; 94% of facilities provided basic hygiene and waste management services; 58 and 2%, respectively, provided basic cleaning and sanitation services. Only 1% of investigated facilities met the basic level for all five WASH dimensions. Advanced service levels were only met for hygiene, waste management, and/or cleaning in 15–38% of facilities. In 33% of health care facilities, drinking-water quality was not in compliance with the national standards. The results revealed that there is a need for increased awareness and efforts to ensure basic provisions for sanitation, environmental cleaning, and drinking-water safety. HIGHLIGHTS: The majority of health care facilities (HCFs) in Autonomous Province Vojvodina provide basic services for drinking-water, hygiene, and health care waste management. Basic provisions for sanitation and environmental cleaning in HCFs emerged as priorities for future action. There is a need to increase efforts to ensure advanced WASH services (observed in up to 38% of facilities), to strengthen the provision of people-centred, quality health care, and outbreak preparedness.